2) y = x/4 - 7 y + 7 = x/4 x = 4(y + 7) Область определения (-оо; +оо) 4) y = (x - 1)^3 x - 1 = корень кубический(y) x = корень кубический(y) + 1 Область определения (-оо; +оо) 5) y = 2/x x = 2/y Область определения (-оо; 0) U (0; +oo) 6) y = 3/(x - 4) x - 4 = 3/y x = 4 + 3/y Область определения (-оо; 0) U (0; +oo)
Answers & Comments
Verified answer
2) y = x/4 - 7y + 7 = x/4
x = 4(y + 7)
Область определения (-оо; +оо)
4) y = (x - 1)^3
x - 1 = корень кубический(y)
x = корень кубический(y) + 1
Область определения (-оо; +оо)
5) y = 2/x
x = 2/y
Область определения (-оо; 0) U (0; +oo)
6) y = 3/(x - 4)
x - 4 = 3/y
x = 4 + 3/y
Область определения (-оо; 0) U (0; +oo)